2023
DOI: 10.1101/2023.03.22.533150
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell transcriptomics reveals that glial cells integrate homeostatic and circadian processes to drive sleep-wake cycles

Abstract: The sleep-wake cycle is determined by circadian and sleep homeostatic processes. However, the molecular impact of these processes and their interaction in different brain cell populations remain unknown. To fill this gap, we profiled the single-cell transcriptome of adult Drosophila brains across the sleep-wake cycle and four circadian times. We show cell type-specific transcriptomic changes with glia displaying the largest variation. Glia are also among the few cell types whose gene expression correlates with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…For example, excitatory and inhibitory neurons had both a higher total number of genes expressed and SJs detected per cell than glial cell types (Table S2, Supporting Information Figure 3A, B). This is consistent with other research, as the fact that neurons express more genes than glia has previously been reported 31 . However, neurons still express more SJs per cell than glial cell types when dividing by the total number of genes expressed (Supporting Information Figure 3C), suggesting neuron-specific genes may be more transcriptionally complex.…”
Section: Resultssupporting
confidence: 94%
“…For example, excitatory and inhibitory neurons had both a higher total number of genes expressed and SJs detected per cell than glial cell types (Table S2, Supporting Information Figure 3A, B). This is consistent with other research, as the fact that neurons express more genes than glia has previously been reported 31 . However, neurons still express more SJs per cell than glial cell types when dividing by the total number of genes expressed (Supporting Information Figure 3C), suggesting neuron-specific genes may be more transcriptionally complex.…”
Section: Resultssupporting
confidence: 94%
“…3i, j). There are, however, subtle hints from an independent transcriptomic study 8 that sleep history may alter levels of mitochondrial components not only in dFBNs but also in R5 neurons of the ellipsoid body, another element of the sleep homeostat 19 .…”
Section: Resultsmentioning
confidence: 99%
“…Sleep pressure, the process variable in sleep homeostasis, currently lacks a physical interpretation. Although prolonged waking is associated with numerous changes in the brain—of neuronal firing patterns 1,2 , the strengths of synaptic connections 3 , metabolite concentrations 4,5 , and metabolic and gene expression programs 6-8 —, it remains generally indeterminable whether these changes are causes or consequences of a growing need for sleep. Perhaps the only realistic opportunity for separating causation from correlation exists in specialist neurons with active roles in the induction and maintenance of sleep 9 ; in these cells, sleep’s proximate (and maybe also its ultimate) causes must interlock directly with the processes that regulate spiking.…”
Section: Introductionmentioning
confidence: 99%